Respostas
respondido por:
0
Basta substituir na equação pelos valores.
A = 5; B = 2,5; e C = 8;
a)
A + B + 3C
5 + 2,5 + 3 . 8
5 + 2,5 + 24
31,5
b)
2A + 4B + C
2 . 5 + 4 . 2,5 + 8
10 + 10 + 8
28
c)
A - 6B + 7C
5 - 6 . 2,5 + 7 . 8
5 - 15 + 56
46
A = 5; B = 2,5; e C = 8;
a)
A + B + 3C
5 + 2,5 + 3 . 8
5 + 2,5 + 24
31,5
b)
2A + 4B + C
2 . 5 + 4 . 2,5 + 8
10 + 10 + 8
28
c)
A - 6B + 7C
5 - 6 . 2,5 + 7 . 8
5 - 15 + 56
46
anakarolineleite:
ta certo?
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás